The person-centred approach to therapeutic change - McMillan, Michael; Sage eBooks (London : SAGE, 2004)
Michael McMillan outlines the main theoretical corner stones of the person-centred approach and then, applying these, describes why change occurs as a result of a person-centred therapeutic encounter.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Client-centered psychotherapy; Electronic books